CLINICAL DIAGNOSTIC CRITERIA FOR THORACIC OUTLET SYNDROME - Коваль, М. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
The article contains the results of the clinical and neurological examination of 16 patients with clinical signs of the thoracic outlet syndrome. The results showed the feasibility of complex instrumental methods of investigation, namely X-ray examination, duplex scanning of vessels of the upper extremities and use of provocation tests because a single test specificity is low.